ANALISIS PENILAIAN KINERJA KEUANGAN BUMN PADA PT.WASKITA KARYA (PERSERO) TBK. TAHUN 2015-2019 - Tiara Monika Hudiyanti, Elfreda Aplonia Lau dan Nurfitriani (Prodi Ilmu Administrasi Negara, 2021)
This study aims to determine and analyze the company's financial performance of PT. Waskita Karya (Persero) Tbk by referring to the Decree of the Minister of BUMN Number: KEP-100 / MBU / 2002 based on the idea that as a state-owned company (BUMN) it should be in a healthy category of performance.The research question examined in this study was whether the financial performance of PT. Waskita Karya (Persero) Tbk in 2015 to 2019 is categorized as healthy?This study was conducted using financial management theory, especially financial performance, which focuses on several aspects of assessment. The analysis tools used are Return On Equity (ROE), Return On Investment (ROI), Cash Ratio, Current Ratio, CollectionPeriods, Inventory Turnover, Total Assets Turnover / Total Asset Turnover (TATO), Total Equity Ratio (TMS) to (TA). ).The results showed that the financial performance of PT. Waskita Karya (Persero) Tbk. assessed based on the Decree of the Minister of BUMN Number: KEP-100 / MBU / 2002 in 2015, 2017 and 2019 were categorized as less healthy. Meanwhile, the financial performance of PT. Waskita Karya (Persero) Tbk. Assessed based on the Decree of the Minister of BUMN Number: KEP-100 / MBU / 2002 in 2016 and in 2018 categorized as healthy.